2020
DOI: 10.5045/br.2020.2020052
|View full text |Cite
|
Sign up to set email alerts
|

Large granular lymphocytes (LGL) in primary Sjögren syndrome (pSS): immunophenotype and review on the pathological role of T cells in pSS

Abstract: We would like to thank Dr. Linda Carli for her help in ensuring a correct follow-up of the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Surprisingly, Friedman et al, in a cohort of 13 patients with SS-associated T-LGL leukemia, observed clonal dominant expansion of CD4+ T-lymphocytes in 4 (31%) patients [ 24 ]. Moreover, out of five patients with pSS-associated T-LGL leukemia, four patients had the typical CD8+ phenotype [ 25 , 27 , 28 ], and in one patient T-LGLs coexpressed CD4 and CD8 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly, Friedman et al, in a cohort of 13 patients with SS-associated T-LGL leukemia, observed clonal dominant expansion of CD4+ T-lymphocytes in 4 (31%) patients [ 24 ]. Moreover, out of five patients with pSS-associated T-LGL leukemia, four patients had the typical CD8+ phenotype [ 25 , 27 , 28 ], and in one patient T-LGLs coexpressed CD4 and CD8 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, the first description of SS with LGL leukemia was presented by Goske et al (1980), who reported on a 52-year-old woman with SS, absolute lymphocytosis, and neutropenia [18]. We found only 39 cases of T-LGL leukemia in SS patients in PubMed to date [7,[19][20][21][22][23][24][25][26][27][28]. Of these, 31 cases of T-LGL leukemia were associated with pSS, 2 cases with sSS (one patient had RA and another had limited scleroderma), and in 6 cases, no information was provided.…”
Section: Discussionmentioning
confidence: 99%
“…In a cohort of patients with SS, stimulation of peripheral blood monocytes by IL-6 revealed increased activation of STAT3 ( 65 ). A phenotype of LGL that has been described in association with SS represents the T emRA subset, which can be seen in the setting of chronic inflammation, but is classically associated with low cell proliferation and high cell death rate compared to LGLs which have prolonged survival due to STAT pathway activation ( 66 ). Overall, these findings highlight overlap between chronic inflammation and autoimmunity as well as the difficulty associated with determining which process is the primary etiology.…”
Section: Activation Of the Jak-stat Pathwaymentioning
confidence: 99%